Rich Malaysia, poor Malaysians - Anas Alam Faizli (Gerakbudaya Enterprise, 2017)
Rich Malaysia, Poor Malaysians grew out of the author's search for enlightening answers to Malaysia's problems as well as his wishes and proposals for a better Malaysia. It is his attempt to bring pressure upon decision makers and policy specialists, as well as to create awareness amongst the public of the need for solutions to the problems plaguing the country.